Assessing the role of aridity-induced vicariance and ecological divergence in species diversification in North-West Africa using Agama lizards. (29th May 2018) - GonÇalves, Duarte V; Pereira, Paulo; Velo-AntÓn, Guillermo; Harris, D James; Carranza, Salvador; Brito, JosÉ C
Abstract: Diversification events in the Sahara–Sahel have mostly been attributed to regional aridification and subsequent arid–humid fluctuations, through vicariance or adaptation. However, no study has attempted to test these contrasting hypotheses. Here, we assess the importance of aridity-induced vicariance (as opposed to adaptation to new conditions) on diversification processes in North-West African Agama lizards. To test the hypothesis of vicariance as the main driver of diversification, we assessed the occurrence of the following three patterns expected to occur under the proposed scenario: (1) prevalent allopatric or parapatric distributions; (2) allopatric climatic refugia coincident with current distributions; and (3) niche similarity decreasing with increasing phylogenetic distance. We also reconstructed the centre of origin and range expansion dynamics for the Sahelian species to verify the congruence of the genetic signal with the vicariance scenario. All patterns expected from a neutral, non-adaptive niche divergence scenario were present. The diffusion models for the Sahelian species identified similar points of origin, corresponding to the areas of highest genetic diversity, topographic heterogeneity and climatic stability. Other patterns, such as mountain-isolated lineages, also indicate isolation by aridity. Our results support vicariance as the main driver of diversification in NW African Agama at both large and local scales. The importance of southern Mauritania for the conservation of biodiversity and the evolutionary process is highlighted.